Sympathetic dysfunction in vasovagal syncope and the postural orthostatic tachycardia syndrome - Lambert, Elisabeth; Lambert, Gavin W. (Frontiers in Physiology, 2014)
Orthostatic intolerance is the inability to tolerate the upright posture and is relieved by recumbence. It most commonly affects young women and has a major impact on quality of life and psychosocial well being. Several forms of orthostatic intolerance have been described. The most common one is the recurrent vasovagal syncope (VVS) phenotype which presents as a transient and abrupt loss of consciousness and postural tone that is followed by rapid recovery. Another common type of orthostatic intolerance is the postural orthostatic tachycardia syndrome (POTS) which is characterized by an excessive rise in heart rate upon standing and is associated with symptoms of presyncope such as light-headedness, fatigue, palpitations and nausea. Maintenance of arterial pressure under condition of reduced central blood volume during the orthostasis is accomplished in large part through sympathetic efferent nerve traffic to the peripheral vasculature. Therefore sympathetic nervous system (SNS) dysfunction is high on the list of possible contributors to the pathophysiology of orthostatic intolerance. Investigations into the role of the SNS in orthostatic intolerance have yielded mixed results. This review outlines the current knowledge of the function of the SNS in both VVS and POTS.